Double Vision - Asian Accounts of Australia - Broinoswki, Alison (ANU Press, 2011)
Do Australians care about what their Asian neighbours think of them - and does it matter if they don't? This collection of essays reveals that admiration for Australia is not widespread, particularly among Japanese and Chinese commentators. And how our Asian neighbours perceive Australia is important: perceptions have a powerful effect on the way different societies respond to one another. As part of the Asian Accounts of Australia project, this volume addresses a much-neglected issue and presents the views of pre-eminent scholars on how Australia is perceived among Chinese and Japanese and what this means for our future. Can Australia make the most of its opportunities to be well regarded and influential in China and Japan or will we be dismissed as a derivative culture, ignorant about our region?